Evaluation of model mind mapping science blended to enhance students students' critical thinking skills - Anggraeni, Desak Made; Prahani, Binar Kurnia; Jatmiko, Budi (Edelweiss Applied Science and Technology, 2024)
This research examines how practicality and effective the integration of the MOODLE system with Mind Mapping Science is in enhancing students' critical thinking skills (CTS). A sample of 127 students from three Indonesian universities was chosen through cluster sampling, and the researchers employed a single-group pre-test-post-test experimental design. Various tools such as CTS assessments, surveys, and observation checklists were utilized in this study. The findings indicate that the combination of the MOODLE-based MMSB model is both effective and efficient. The analysis process involved determining the mean score, conducting a paired t-test, calculating the N-gain value, and evaluating questionnaire feedback on the implementation of the MOODLE-based MMSB model. Each of these steps demonstrated reliability, meeting the “very good” standard and confirming its practicality. The effectiveness of the model is highlighted by a significant increase in CTS scores at a 5% significance level. The average N-gain results were consistent across different classes at each university. Student feedback was very effective, indicating a strong interest in applying this model. In conclusion, the results suggest that combining the MOODLE system with the MMSB model leads to improved CTS and greatly supports structured learning processes in various disciplines.